2020
DOI: 10.1186/s12985-020-01447-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and genotypic characterization of HBV among low risk voluntary blood donors in Nairobi, Kenya

Abstract: Background Hepatitis B virus (HBV) causes significant morbidity and mortality globally primarily due to its ability to cause hepatitis, liver cirrhosis and hepatocellular carcinoma. The Kenya National Blood Transfusion Services screens for Hepatitis B antibodies using the chemiluminescent microparticle immunoassay method. This test does not inform on the genotypic characteristics of the virus or the actual presence of the virus in blood. This study therefore sought to determine the serologic and genotypic prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…[40][41][42][43][44] This study revealed the overall magnitude of three common viral TTIs in the donor population was 14.4%. This finding is somewhat similar to that of studies conducted in Easter region, Jigjiga 11.5% 50 and Northwest region, Felege Hiwot 13.3% 17 in Ethiopia and other developing countries; 12.0% in Kenya, 7 13.7% in Eritrea, 20 13.0% in Nigeria 5 but lower studies reported in other locations of south Ethiopia; 29.5% in Sodo Wolaita, 11 and 43.2% in Bahir Dar 8 and other African countries; 29.85% in Burkina Faso, 30 21.2% in Cameroon 32 and 37.4% in Equatorial Guinea. 49 This is probably because of the actual differences in study, population, duration, variation in occupation, and geographical differences of the study populations; moreover, the prescreening procedure may also play a role in the observed variations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[40][41][42][43][44] This study revealed the overall magnitude of three common viral TTIs in the donor population was 14.4%. This finding is somewhat similar to that of studies conducted in Easter region, Jigjiga 11.5% 50 and Northwest region, Felege Hiwot 13.3% 17 in Ethiopia and other developing countries; 12.0% in Kenya, 7 13.7% in Eritrea, 20 13.0% in Nigeria 5 but lower studies reported in other locations of south Ethiopia; 29.5% in Sodo Wolaita, 11 and 43.2% in Bahir Dar 8 and other African countries; 29.85% in Burkina Faso, 30 21.2% in Cameroon 32 and 37.4% in Equatorial Guinea. 49 This is probably because of the actual differences in study, population, duration, variation in occupation, and geographical differences of the study populations; moreover, the prescreening procedure may also play a role in the observed variations.…”
Section: Discussionsupporting
confidence: 89%
“…4,5 About 350 million people worldwide are chronically infected with HBV, more than 71 million with HCV, and 38 million with HIV. 6,7 The prevalence of TTIs among blood donors is widely used as an indicator of the problem. [8][9][10] In several settings, HBV, HCV, and HIV are the major TTIs.…”
Section: Introductionmentioning
confidence: 99%
“…This research was aimed at establishing the circulating hepatitis B virus genotypes in a low and a high endemic region of Uganda in order to give a plausible explanation for the regional differences in disease burden. The nucleotide sequence analysis of the hepatitis B virus DNA polymerase gene in all patient samples from the low and high endemic regions detected genotypes A and D consistent with earlier studies in other African countries including Tunisia [ 27 ], Gambia, Nigeria, Congo, Rwanda, Cameroon [ 34 ], Egypt [ 35 ], Central African Republic [ 36 ], South Africa [ 20 ], Morocco [ 37 ], Kenya [ 38 ], and Uganda [ 9 ]. Besides, a high proportion of the D/E recombinant genotype mildly reported in Uganda by Zirabamuzaale and Ocama [ 9 ] has been prominently reported in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The HBV seroprevalence in voluntary blood donors was marginally higher compared to the 2.3% seroprevalence recorded in the same group in a study carried out in Nairobi, Kenya using the chemiluminescent microparticle immunoassay (CMIA) [8] and similar to (3.46%) seroprevalence from a study carried out in Kisumu, Homabay and Siaya Counties, Kenya using ELISA and confirmed by CMIA [7].…”
Section: Discussionmentioning
confidence: 47%
“…Kenya has been categorized with other sub-Saharan African countries with a HBV infection burden of chronic states of intermediate range (2% -7%) and high (≥8%) [4]. Studies have shown HBV infection disparity in Kenya among various study populations, with 5.1% prevalence in areas near Nairobi among rural settler community, 15.3% in Turkana County among pregnant women [6], 3.46% in Kisumu, Homabay and Siaya Counties [7] and 2.3% in Nairobi [8] among blood donors. Diagnosis of HBV is routinely done by measurement of various HBV specific antigens and antibodies.…”
Section: Introductionmentioning
confidence: 99%